Modelos de aglomera????o da nova geografia econ??mica (uma an??lise em painel para os estados brasileiros) - Sousa, Camila Alves de (2015)
The text sought to explore and apply the models of agglomeration of the New Economic Geography for the Brazilian states. The relevant question is how the effects of agglomeration can affect economies. For this, were derived clustering models to verify the socalled: Price Index Effect Effect Market Place and Lack of Black Hole for the period 1994 to 2007. The estimates were made using the econometric analysis of panel data with fixed effects for the twenty-seven states. The results were as expected for the price index effect, statistically significant, proving the agglomeration proposition, and a drop in prices caused by increased competition and also the lowest cost of transport in the regions. For the local market index, the results showed that the market where the sector is higher there will be greater demand for employment. It was also possible to state that for the Brazilian economy there is not empirical evidences of the black hole condition.